Construction of the first genetic linkage map of Japanese gentian (Gentianaceae) - Nakatsuka, Takashi (BioMed Central, 2012)
BACKGROUND: Japanese gentians (Gentiana triflora and Gentiana scabra) are amongst the most popular floricultural plants in Japan. However, genomic resources for Japanese gentians have not yet been developed, mainly because of the heterozygous genome structure conserved by outcrossing, the long juvenile period, and limited knowledge about the inheritance of important traits. In this study, we developed a genetic linkage map to improve breeding programs of Japanese gentians. RESULTS: Enriched simple sequence repeat (SSR) libraries from a G. triflora double haploid line yielded almost 20,000 clones using 454 pyrosequencing technology, 6.7% of which could be used to design SSR markers. To increase the number of molecular markers, we identified three putative long terminal repeat (LTR) sequences using the recently developed inter-primer binding site (iPBS) method. We also developed retrotransposon microsatellite amplified polymorphism (REMAP) markers combining retrotransposon and inter-simple sequence repeat (ISSR) markers. In addition to SSR and REMAP markers, modified amplified fragment length polymorphism (AFLP) and random amplification polymorphic DNA (RAPD) markers were developed. Using 93 BC(1) progeny from G. scabra backcrossed with a G. triflora double haploid line, 19 linkage groups were constructed with a total of 263 markers (97 SSR, 97 AFLP, 39 RAPD, and 30 REMAP markers). One phenotypic trait (stem color) and 10 functional markers related to genes controlling flower color, flowering time and cold tolerance were assigned to the linkage map, confirming its utility. CONCLUSIONS: This is the first reported genetic linkage map for Japanese gentians and for any species belonging to the family Gentianaceae. As demonstrated by mapping of functional markers and the stem color trait, our results will help to explain the genetic basis of agronomic important traits, and will be useful for marker-assisted selection in gentian breeding programs. Our map will also be an important resource for further genetic analyses such as mapping of quantitative trait loci and map-based cloning of genes in this species.